Comparing satisfaction of trauma patients 55 years or older to their caregivers during palliative care: Who faces the burden?. Issue 2 (February 2021) - McGraw, Constance; Vogel, Rebecca; Redmond, Diane; Pekarek, Jennifer; Tanner, Allen; Lynch, Neal; Bar-Or, David
Abstract : BACKGROUND: Many studies report on the patient-caregiver relationship during palliative care (PC); however, this relationship has yet to be examined following traumatic injury. METHODS: This prospective cohort study included trauma patients (≥55 years) and their primary caregivers admitted at two level I trauma centers for 2 years (November 2016 to November 2018), who received PC and who completed satisfaction surveys before discharge; surveys were analyzed by four domains: information giving, availability of care, physical care, and psychosocial care, and by PC assessments: consultations, prognostications, formal family meetings (FFMs), and advanced goals of care discussions. The primary outcome was the percentage of patients and caregivers who were satisfied (defined as ≥80%) and was analyzed using McNemar's test. Adjusted mixed models identified PC assessments that were associated with satisfaction scores ≥80% for patients and caregivers. RESULTS: Of the 441-patient and 441-caregiver pairs, caregivers were significantly less satisfied than patients during prognostications (information giving, physical care), FFMs (information giving, physical care), and consultations (physical care), while caregivers were significantly more satisfied than patients during advanced goals of care discussions (availability of care, psychosocial care). After adjustment, significant predictors of caregiver satisfaction (≥80%) included longer patient hospital length of stay (>4 days), caring for a male patient (physical care, availability of care), higher caregiver age (≥55 years; availability of care), and higher patient age (≥65 years; psychosocial care). Conversely, all PC assessments decreased odds of satisfaction for caregivers in every domain except physical care. Significant predictors of higher patient satisfaction included FFMs (for every domain) and PC consultations (psychosocial care), and decreased odds included advanced goals of care discussions and prognostication assessments (information giving, psychosocial care). CONCLUSIONS: Palliative care increased satisfaction of patients, especially family meetings and consultations, while assessments were predictive of lower caregiver satisfaction, suggesting that caregivers may be experiencing some of the patient burden. LEVEL OF EVIDENCE: Therapeutic/Care Management, level IV. Abstract : Supplemental digital content is available in the text.